Propensity score adjusted analysis of patients with isolated locoregional recurrence versus de novo locally advanced NSCLC treated with definitive therapy. (July 2020) - Friedes, Cole; Mai, Nicholas; Fu, Wei; Hu, Chen; Han, Peijin; Marrone, Kristen A.; Voong, K. Ranh; Hales, Russell K.
Highlights: 65 Patients with iLR are compared to a cohort of 302 patients with de novo LA-NSCLC. iLR group treated with either surgery or RT at diagnosis, salvaged with definitive local therapy. There was no difference in PFS, TTDM, or OS between the iLR and LA-NSCLC group. Patterns of failure did not differ between groups. Older patients with iLR who received salvage therapy had worse OS. Abstract: Objectives: Definitive intent treatment of isolated locoregional recurrence (iLR) for non-small cell lung cancer (NSCLC) is becoming more common. This study explores outcomes associated with the definitive local treatment of iLR and compares these outcomes to newly diagnosed locally advanced NSCLC (LA-NSCLC) patients. Materials and methods: Patients with NSCLC treated with curative therapy between 2008 and 2019 at a tertiary academic institution were screened for iLR treated with subsequent definitive salvage therapy. Progression free survival (PFS), time to distant metastasis (TTDM), and overall survival (OS) were calculated via Kaplan–Meier methodology. Clinical outcomes were compared to a separate group of patients with de novo LA-NSCLC after adjusting for propensity score (PS). Results: Sixty five cases of definitively salvaged iLR were compared to 302 patients with de novo LA-NSCLC. Most patients were treated with chemoradiotherapy (83.1% in iLR, 74.5% in LA-NSCLC). The median PFS, TTDM, and OS for the iLR cohort was 16.7 months (95% CI: 9.6–24.7), 35.8 months (95% CI: 17.1-NR), and 49.5 months (95% CI: 30.1-NR), respectively. After adjusting for PS, the iLR group was no different from the LA-NSCLC group in risk for progression (HR 0.78, 95% CI: 0.53–1.16, p  = 0.22), distant metastasis (HR 0.81, 95% CI: 0.52–1.27, p  = 0.36), or death (HR 0.90, 95% CI: 0.47–1.73, p  = 0.75). Patterns of failure did not different significantly between groups. In the iLR cohort, patients with older age (HR 1.06, 95 CI: 1.01–1.10, p  = 0.01) had a higher risk of death on multivariate analysis. Conclusion: To our knowledge, this is the first report that compares the definitive treatment of iLR to de novo LA-NSCLC. When treated with definitive local therapy, patients with iLR had no difference in clinical outcomes from de novo LA-NSCLC. The use of curative local therapy according to a LA-NSCLC paradigm is advisable in patients with iLR of NSCLC for whom definitive therapy is feasible.